A case study exploring an occupational perspective of social inclusion among young adults dually afflicted with substance use disorder and HIV/AIDS in Zimbabwe - Nhunzvi, Clement (Department of Health and Rehabilitation Sciences, 2022)
Background: Curtailing adverse social determinants of health is pivotal to achieving the 2030 Agenda for Sustainable Development`s vision for a healthy and inclusive society. In Zimbabwe, fulfilling Vision 2030 may involve adopting socially inclusive approaches, particularly for young people dually afflicted with HIV and substance use disorders. However, social inclusion remains conceptually unclear and underutilized in relation to marginalized groups in low resource settings. This study sought to explore and understand how dually afflicted young adults with substance use disorders and HIV in Zimbabwe experienced and negotiated their social inclusion. Methods: This study utilised a qualitative instrumental case study design. Primary qualitative and quantitative data were collected to develop a thorough understanding of the case of an occupational perspective of social inclusion among dually afflicted young adults in Zimbabwe. The multiple methods used in this study included: i) narrative inquiry with five dually afflicted young adults; ii) in-depth interviews with five key informants; iii) document analysis of seven policies; and, iv) exploratory cross-sectional survey of social inclusion and associated factors (n=105). These multiple methods and sources contributed to the study`s trustworthiness. Multi-level case study analysis was applied as follows; 1st level: narrative analysis of each of the five young adults` stories, descriptive analysis of key informant interviews, document analysis and descriptive statistical analysis of the cross-sectional survey data. 2nd level: thematic case analysis drawing from all four data sources. 3rd level: theorised conceptual occupational constructs. Findings: Five narratives illustrated how using agency and having occupational choices were central to the young adults` experience and negotiation of social inclusion. The overarching Case theme was “Navigating an already troubled life: Striving for belonging and well-being”. This consists of three categories: 1) Dealing with a context of mixed realities, 2) Trying to adjust to new challenges and, 3) Life on the margins. These findings show how dually afflicted young adults in Zimbabwe respond and resist the influences of dominant discourses through dynamic and interconnected actions that shape their realities. Conclusion: The study describes and explains how dually afflicted young adults experienced and negotiated their social inclusion. The data affirms the role of agency and proposes a more critical view of occupational choice, activist occupational choice, in understanding social inclusion. As an emergent concept it is categorized by occupational choices, largely defying standard norms of engagement, and aims to break away from oppressive systems and problematic situations. Recognising the diverse manifestation of agency yields an appreciation for how occupations that are indigenous, collective, and resist oppression contributes to experiences of social inclusion.